EFECTO DE LA EMERGENCIA, CRECIMIENTO Y PRODUCCIÓN DEL CULTIVO DE PIMIENTO ROJO (Capsicum annuum) CON LA BIOFERTILIZACIÓN DEL ALGA MARINA (Ascophyllum nodosum) - GONZABAY NAVARRETE, KATTYA VERONA (2023)
The objective of this work was to determine the emergence, growth and production of the red bell pepper (Capsicum annuum) crop by applying biostimulants based on seaweed Ascophyllum nodosum at different doses, with the purpose of evaluating the use of ecological alternatives such as seaweed and how these can contribute to sustainable practices in the production of red bell pepper. The present study was carried out at the "La María" University Campus of the UTEQ. The design used was a DCA, consisting of 5 treatments and 4 replicates divided into concentrations of 0%, 100%, 75%, 50% and 25% of Ascophyllum nodosum seaweed extract. For the comparison of measurements between treatments, the 5% Tukey test was used. The results in trial 1 showed that T1 with a dose of 100 %, had a significant influence on seed emergence, in contrast to the parameters of height, root length, leaf length and diameter, dry and fresh biomass, where there were non-significant statistical differences, with the control showing better parameters. nodosum obtained better agronomic and productive parameters in relation to the control, obtaining higher income, concluding that seaweed extracts such as Ascophyllum nodosum have a significant influence on the agronomic-productive parameters of the red bell pepper crop, maintaining the use of sustainable practices to improve the quality of the crops.